Efektivitas Pelaksanaan Program Jumantik oleh Kader Surabaya Hebat (KSH) di Kelurahan Pakis Kecamatan Sawahan Kota Surabaya - Reviandani, Oktarizka; Ardiningrum, Sekar Damayanti; Annisa, Dea; Khoirril, Oktavia Putri; Nurmaulidya, Salsabila (IAI Nasional Laa Roiba Bogor, 2025)
DBD has become a crucial health problem in Indonesia especially the city of surabaya and it is predicted to continue to rise in the future. Pakis Village was not free of the danger of DBD. It was recorded in 2016 to 2019 that there were 20 cases of DBD in Pakis Village and it was a large number. Government established a Kader Surabaya Hebat (KSH) to solve the DBD problem. Kader Surabaya Hebat (KSH) moves to perform a jumantic program by applying some detailed checking and reviewing. The aim of this study is to measure the effectiveness of the jumantic program in dealing with DBD problems especially in households of ferns uses the theory of measuring the effectiveness of the program according to Edhy Sutrisno. The study involves a qualitative method with a descriptive approach. Data retrieval techniques using observation and interviewing informants. The results of this study showed Kader Surabaya Hebat (KSH) success in reaching all of the measurement of the program's effectiveness: understanding of the program, exactly the point, the right time, the attainment of its purpose, and the obvious change. Based on the fifth indicator of achievement, the jumantik program performed by Kader Surabaya Hebat (KSH) Pakis Village is said to be effective. However, Kader Surabaya Hebat (KSH) has had a number of difficulties in accessing the Aplikasi Sayang Warga (ASW) from the website has arrived unresponsibly, display or writing on the application is too small and cadre still poorly technologically.